Recent Progress in Rechargeable Sodium‐Ion Batteries: toward High‐Power Applications. Issue 32 (18th February 2019) - Pu, Xiangjun; Wang, Huiming; Zhao, Dong; Yang, Hanxi; Ai, Xinping; Cao, Shunan; Chen, Zhongxue; Cao, Yuliang
Abstract: The increasing demands for renewable energy to substitute traditional fossil fuels and related large‐scale energy storage systems (EES) drive developments in battery technology and applications today. The lithium‐ion battery (LIB), the trendsetter of rechargeable batteries, has dominated the market for portable electronics and electric vehicles and is seeking a participant opportunity in the grid‐scale battery market. However, there has been a growing concern regarding the cost and resource availability of lithium. The sodium‐ion battery (SIB) is regarded as an ideal battery choice for grid‐scale EES owing to its similar electrochemistry to the LIB and the crust abundance of Na resources. Because of the participation in frequency regulation, high pulse‐power capability is essential for the implanted SIBs in EES. Herein, a comprehensive overview of the recent advances in the exploration of high‐power cathode and anode materials for SIB is presented, and deep understanding of the inherent host structure, sodium storage mechanism, Na + diffusion kinetics, together with promising strategies to promote the rate performance is provided. This work may shed light on the classification and screening of alternative high rate electrode materials and provide guidance for the design and application of high power SIBs in the future. Abstract : The sodium‐ion battery (SIB) is an ideal choice for large‐scale energy storage, and high pulse‐power capability is essentially required for its applications. The recent progress of high‐power SIBs including cathodes, anode materials, electrolytes, and aqueous systems is reviewed. Special attention is given on understanding the inherent host structure, sodium storage mechanism, Na + diffusion kinetics, and strategies to promote the rate performance.